PENGARUH STRUKTUR KEPEMILIKAN DAN MODAL INTELEKTUALTERHADAP NILAI PERUSAHAAN DENGAN KEPUTUSANKEUANGAN DAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Otomotif di Bursa Efek Indonesia Tahun 2013-2015) - Yosep Agave Pakpahan; Emrinaldi '; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to demonstrate empirically the direct and indirect influence of the structure of ownership and intellectual capital to the firm value with financial decisions and financial performance as an intervening variable. The population in this study is the automotive company listed on the BEI in 2013- 2015. The sampling method used in this research is purposive sampling. Data analysis was performed using normality test and classical assumption test consisting of Multicolinearity, Heteroskidastity test, and Autocorrelation test. This study used path analysis with SPSS 17.0. This study uses a test of determination. Institutional ownership is a proxy of the ownership structure and intellectual capital measured using VAICTM. Funding decisions are proxies of financial decisions that are measured using the DER and financial performance is measured by using ROA. The dependent variable is the firm value is measured by using a PBV. The results of this study indicate that institutional ownership and intellectual capital directly and indirectly not affect funding decisions but intellectual capital directly affect financial performance. Institutional ownership directly affects to the firm value. funding decisions do not affect financial performance. funding decisions and financial performance are not able to mediate the institutional ownership and intellectual capital on firm value.Keywords: institutional structure, intellectual capital, funding decisions, financial performance, firm value.